Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

when solving 1st order linear differential equations, we have some common method.

I have some questions about the common methods.

for example $\dfrac{dy}{-y + 5} = dt$ , why can we integrate on both side to get the equation of $y$? More specifically, we have different things to integrate, $y$ and $t$ respectively, why can we just integrate on both side? What's the underlying reason here?

Also when we get $\,\ln |5 - y| = -t + C,\,$ why can we immediately get $\,5- y = e^{-t + C}\,$ and get rid of the absolute sign? There is no information about the range of $y$, why can we do that? Thanks

share|cite|improve this question
up vote 7 down vote accepted

Your confusion stems from a lack of knowledge of what the notation means. When we write $$ \frac{dy}{-y+5} = dt $$ what we mean is $$ \frac{dy}{dt} \frac{1}{-y+5} = 1 $$ and we then integrate both sides in $t$, (recall $y=y(t)$). The reason it looks like we are integrating the left side in terms of $y$ is because of the chain rule. The equation being separable means we can write it like $$ f(y)dy = g(t)dt $$ which means $$ \frac{dy}{dt} f(y(t)) = g(t). $$

But by the chain rule , if $F,G$ antiderivatives of $f,g$, then we have $$ \frac{d}{dt}(F(y(t)) = f(y(t))\frac{dy}{dt} $$ and integrating in $t$ gives $$ F(y(t)) = G(t)+C $$ which looks like you integrated in $y$ on the left and $t$ on the right in the sloppy notation.

As for why you can get rid of absolute values, you can't. You must consider $5-y = e^{-t+C}$ as well as $y-5 = e^{-t+C}$. This gives us $$ y = 5-e^C e^{-t},~~ y= 5 + e^C e^{-t} $$ as valid solutions. But note that $e^C$ is an arbitrary positive constant, and $-e^C$ is an arbitrary negative constant, so both solutions may be conglomerated into the shorter form $$ y = 5 + ce^{-t} $$ where $c$ is an arbitrary nonzero constant.

If the original question was given as $y' = -y+5$, that is YOU divided by $-y+5$, then you must also check that the constant solution $y=5$ works, so that $y=5+ce^{-t}$ is valid for all $c \in \mathbb{R}$. If the equation was given in the form with $-y+5$ in the denominator already, i.e. you did not introduce division by $-y+5$, then we leave the answer with $c \neq 0$ as the statement would not make sense if $y=5$.

share|cite|improve this answer

Actually, here how it goes, you have: $$ \frac{1}{5-y}\frac{dy}{dt}=1, $$ and you integrate both sides with respect to $t$ and then use the substitution in the left hand side: $$ \int \frac{1}{5-y(t)}\frac{dy}{dt}dt=\int \frac{1}{5-y}{dy}=\int dt, $$ from which $$ -\ln |5-y|=t+C. $$ After you get $$ |5-y|=e^{-t-C}=C_1e^{-t}, $$ where $C_1$ is supposed to be positive. After that $$ 5-y=\pm C_1e^{-t}=C_2e^{-t}, $$ where $C_2$ can be now arbitrary (except for zero, however you can check that $y=5$ is a solution of $y'=5-y$, which means that $C_2$ is an absolutely arbitrary constant).

share|cite|improve this answer
Thanks! This makes more sense but some people still insist the method that I indicated. Do u have any idea about that method's corrctness? and why can we get rid of the absolute sign ? – Frank Xu Jan 5 '13 at 0:40
@FrankXu See the edit – Artem Jan 5 '13 at 0:42

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.